Interventional inflammatory bowel diseases endoscopic management and treatment of complications - Shen, Bo (Of Cleveland Clinic Foundation) (Elsevier, Academic Press, 2018)
Interventional Inflammatory Bowel Diseases: Endoscopic Management and Treatment of Complications covers the preparation, principle, techniques, and damage control of complications in endoscopic therapy, providing the ultimate guidance in endoscopic management of IBD. With contributions from a panel of international leading experts in the field, perspectives are included from GI pathologists, GI radiologists, gastroenterologists, advanced endoscopists, IBD specialists and colorectal surgeons. Recommendations from experts are also included within each chapter. By bridging medical and surgical treatment modalities for IBD, this is the perfect reference for GI researchers, medical students, therapeutic GI endoscopists, IBD specialists, surgeons and advanced health care providers.